Miss Wick and the duke dilemma - Marsh, Violet (Forever, 2026)
"Eoin Aucourte, the newly minted Duke of Foxglen, always played by his grandfather's rules. But now that the old man is dead, Eoin's first decision is to track down his long-lost mother. The only problem? He'll have to visit the infamous Black Sheep Coffeehouse to begin his search. Rumor has it that the owner, Miss Hannah Wick, knows all the gossip from the dingiest St. Giles alleyways to the glittering ballrooms of Mayfair. But the whip-smart daughter of a pirate also has a way of making Eoin forget all the lessons on propriety that his grandfather ruthlessly instilled in him. The Duke of Foxglen represents everything Hannah disdains about the nobility. Even worse, his grandfather exiled her papa from England, setting her father on the course of piracy and endangering her entire family. Seeing an opportunity to seek vengeance on his family, Hannah pretends to "help" the shy, surprisingly handsome duke-but soon realizes Eoin may be the first truly honorable noble she's ever met. With every clue they uncover, their search intensifies... and so does their attraction. But with so many secrets between them, does love even stand a chance?"-- Provided by publisher.